O12.6 Quality assessment of the enhanced gonococcal antimicrobial surveillance program in thailand, 2015–2016. (8th July 2017) - Weston, Emily; Lertpruek, Sirirat; Tongtoyai, Jaray; Buasakul, Prisana; Sukwicha, Wichuda; Chonwattana, Wannee; Weston, Emily; Dunne, Eileen; Sirivongrangsan, Pachara
Abstract : Introduction: Antimicrobial resistant Neisseria gonorrhoea (NG) is important to monitor as a potential global public health threat. The Thailand Enhanced Gonococcal Antimicrobial Surveillance Programme (EGASP) was started in November 2015 as a collaboration between the Thailand Ministry of Public Health, the US Centres for Disease Control and Prevention and the World Health Organisation. As a part of this surveillance activity, Thailand conducted an internal quality assessment (QA) of clinical and laboratory data in order to improve surveillance data quality. Methods: EGASP Thailand occurs in 2 sentinel sites: Bangrak Hospital and Silom Community Clinic at Tropical Medicine. Men with symptoms had demographic and clinical data collected as well as a urethral specimen collected for NG culture. A random selection of 10% of EGASP IDs were sampled from November 2015 to June 2016. We assessed clinical and laboratory findings using a standardised review tool that compared the EGASP database to source documents. We describe key findings from the review activities. Results: Overall, 699 specimens were collected for EGASP and 70 (10%) EGASP IDs were randomly sampled by SQL command for review. Results from the quality review included: differences in laboratory findings (6%), differences in interpretation of the clinical abstraction tool between sentinel sites (10%), missing data in the EGASP database after chart abstraction and laboratory testing (14%), differences in the recording of clinical data (19%), and differences in the recording and tracking of laboratory variables (47%). As a result of this evaluation, staff updated missing data on records sampled, conducted an overall refresher training for staff and established a new laboratory tracking process. Conclusion: EGASP Thailand is the first coordinated global project to conduct comprehensive surveillance for NG resistance from symptomatic men. An internal QA helped direct efforts to improve surveillance. Ongoing NG surveillance and periodic quality assessments help ensure high quality surveillance data.